Telephone risk-based eligibility assessment for low-dose CT lung cancer screening. Issue 10 (21st July 2022) - Dickson, Jennifer L; Hall, Helen; Horst, Carolyn; Tisi, Sophie; Verghese, Priyam; Mullin, Anne-Marie; Teague, Jonathan; Farrelly, Laura; Bowyer, Vicky; Gyertson, Kylie; Bojang, Fanta; Levermore, Claire; et al.
Abstract : Eligibility for lung cancer screening (LCS) requires assessment of lung cancer risk, based on smoking history alongside demographic and medical factors. Reliance on individual face-to-face eligibility assessment risks inefficiency and costliness. The SUMMIT Study introduced a telephone-based lung cancer risk assessment to guide invitation to face-to-face LCS eligibility assessment, which significantly increased the proportion of face-to-face attendees eligible for LCS. However, levels of agreement between phone screener and in-person responses were lower in younger individuals and minority ethnic groups. Telephone-based risk assessment is an efficient way to optimise selection for LCS appointments but requires further iteration to ensure an equitable approach.